Conquering the professional learning network labyrinth: what is required from the networked school leader?. (26th May 2020) - Brown, Professor Chris; Flood, Jane
ABSTRACT: Increasingly, policymakers, school and school system leaders are turning to Professional Learning Networks (PLNs) as a means to achieve bottom-up educational improvement at scale (Brown and Poortman, 2018). Likening the leadership challenges of establishing PLNs to conquering a labyrinth, this paper draws on extant literature to explore one key factor thought vital to the success of PLNs: the role of school leaders in creating a two-way link between PLNs and schools. Drawing on Bauman's [2012. Liquid Modernity . Cambridge: Polity Press] notion of liquid modernity to ground the emergence of education networks within wider trends affecting society, this theoretical paper provides a conceptual exploration of the role of school leaders in maximising the benefits of networked ways of working for their school. Settling on three vital network leadership functions of formalising, prioritising and mobilising PLN engagement, the paper concludes by establishing some of the key areas school leaders need to consider if they are to successfully negotiate the PLN maze. Also detailed are the suggested 'lessons' school and system leaders should heed to maximise the impact of PLNs for all schools involved.